Contribution of Bowman layer to corneal biomechanics. Issue 7 (July 2021) - Torres-Netto, Emilio A.; Hafezi, Farhad; Spiru, Bogdan; Gilardoni, Francesca; Hafezi, Nikki L.; Gomes, Jose Alvaro P.; Randleman, J. Bradley; Sekundo, Walter; Kling, Sabine
Abstract : Bowman layer does not enhance significantly the tensile elasticity of a thin corneal lamella, which may have implications in both refractive laser surgery and Bowman layer transplantation for keratoconus. Abstract : Purpose: To compare the elastic modulus of thin corneal lamellas using 2D stress–strain extensometry in healthy ex vivo human corneal lamellas with or without the presence of Bowman layer. Setting: Center for Applied Biotechnology and Molecular Medicine, University of Zurich, Switzerland; ELZA Institute, Dietikon, Switzerland; Department of Ophthalmology, Philipps University of Marburg, Germany. Design: Prospective experimental laboratory study. Methods: Healthy human corneas were stripped of Descemet membrane and the endothelium for Descemet membrane endothelial keratoplasty. After epithelium removal, corneas were divided into 2 groups. In Group 1, Bowman layer was ablated with an excimer laser (20 μm thick, 10 mm). In Group 2, Bowman layer was left intact. Then, a lamella was cut from the anterior cornea with an automated microkeratome. Elastic and viscoelastic material properties were analyzed by 2D stress–strain extensometry between 0.03 and 0.70 N. Results: Twenty-six human corneas were analyzed. The mean lamella thickness was 160 ± 37 μm in corneas with Bowman layer and 155 ± 22 μm in corneas without. No statistically significant differences between flaps with and without Bowman layer were observed in the tangential elastic modulus between 5% and 20% strain (11.5 ± 2.9 kPa vs 10.8 ± 3.7 kPa, P > .278). Conclusions: The presence or absence of Bowman layer did not reveal a measurable difference in corneal stiffness. This may indicate that the removal of Bowman layer during photorefractive keratectomy does not represent a disadvantage to corneal biomechanics.